2022
DOI: 10.3390/insects13020136
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci as Dominant Xylose Utilizing Lactic Acid Bacteria in Eri Silkworm Midgut and the Potential Use of Enterococcus hirae as Probiotic for Eri Culture

Abstract: A total of 51 pentose utilizing lactic acid bacteria (LAB) were isolated from acid-forming bacteria in the midgut of healthy mature Eri silkworm using de Man, Rogosa and Sharpe (MRS) agar containing 10 g/L xylose (MRS-xylose) as the carbon source supplemented with 0.04% (w/v) bromocresol purple. Further analysis of 16S rRNA gene sequences revealed the highest prevalence of up to 35 enterococci isolates, which included 20 isolates of Enterococcus mundtii, followed by Entercoccus faecalis (eight isolates), Weiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Additionally, Lactococcus and Enterococcus were the two most abundant of larval gut samples. Some cellulolytic Enterococcus strains were found in the eri silkworm larvae, Samia ricini ( MsangoSoko et al, 2021 ; Unban et al, 2022 ), since Enterobacteriales have been observed to assist in the breakdown of plant cell wall compounds, including pectin ( Shil et al, 2014 ; Blankenchip et al, 2018 ). Therefore, Enterococcus may have more important role in cellulose degradation in G. cantor ( Robert and Bernalier-Donadille, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lactococcus and Enterococcus were the two most abundant of larval gut samples. Some cellulolytic Enterococcus strains were found in the eri silkworm larvae, Samia ricini ( MsangoSoko et al, 2021 ; Unban et al, 2022 ), since Enterobacteriales have been observed to assist in the breakdown of plant cell wall compounds, including pectin ( Shil et al, 2014 ; Blankenchip et al, 2018 ). Therefore, Enterococcus may have more important role in cellulose degradation in G. cantor ( Robert and Bernalier-Donadille, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus is a kind of bacteria that specially intergrowth the gut of silkworm and has the function like synthesizing amino acids [ 17 ], and suppresses sucrose-induced hyperglycemia [ 18 ]. Meanwhile, the genus has antimicrobial activity [ 16 ], and its abundance will also could be affected by other harmful bacterial infections [ 44 ]. Therefore, the increased abundance of Enterococcus in our result might indicate an immune response to wax feeding of silkworm.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the anti-insect effect of sugarcane wax, setting up a feeding experiment with a model animal is a convenient and effective method. The silkworm ( Bombyx mori ) is a promising model animal for assessing health safety and environmental pollutants in many studies [ 16 , 17 , 18 , 19 , 20 , 21 ], and it can be an alternative to sugarcane borer ( Diatraea sacharalis ) in feeding trail experiments based on the following reasons. First, the silkworm and sugarcane borer are members of the same order (Lepidoptera) and the silkworm is sensitive to chemical compounds such as pesticides, drugs and heavy metals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S6b), but it is an important human pathogen that causes various diseases, has strong drug resistance, and can survive under harsh conditions ( 41 ). In silkworms, it is often the dominant strain ( 42 44 ). Inoculation of silkworm larvae with E. mundtii may have a negative impact on the host response to chlorpyrifos ( 45 ).…”
Section: Discussionmentioning
confidence: 99%